An Exploratory Study On RÄ±sk Management DÄ±sclosure On ConventÄ±onal CommercÄ±al Banks In IndonesÄ±a - Pangestuti, Dewi Cahyani; Hunah, Gitna Revania (Department of Management, Faculty of Economics and Business, Brawijaya University, 2021)
In the last few years of The Global Risks Report 2020 made Covid-19 ranked 10th as a risk that has a big influence on the world and it can be classified into the relevant type of risk management disclosure. This type of risk is very influential on operational risk because it can interfere with all aspects to the running of the company. Therefore the researchers interest in this phenomenon that related to conventional commercial banks on the Indonesia Stock Exchange (IDX) and reviewed on aspects of internal factors that are sensitive to the rise and fall of the company's risk management disclosure figures, such as company size, profitability, and leverage. The study examined the disclosure of conventional commercial bank risk management with saturated sampling methods and used data from forty-one companies during the period from 2017 to 2019. The results showed that the size of the company has an influence on the rise and fall of risk management disclosure. The study also concluded that profitability does not have enough influence on all aspects of risk management disclosure. Similarly, in terms of leverage, this study obtained results that had no effect on risk management disclosure.